Vibro-Impact Type Triboelectric Energy Harvester for Large Amplitude and Wideband Applications. (November 2015) - Chen, J M; Bu, L; Xu, W Y; Xu, B J; Song, L
Abstract: This paper reports the design, fabrication and testing of a novel vibro-impact type triboelectric energy harvester. The dynamics of vibro-impact converts external vibration to large contact force for triboelectric power generation. Strong nonlinearities are measured for this vibro-impact system, and wideband frequency response under diverse structural parameters are analyzed. The proposed device is applied in two large amplitude scenarios, and generates maximal peak-to-peak voltage of 18V in foot swinging condition @2Hz 30cm, and maximal peak-to-peak voltage of 45 V in arm swinging condition during running @5Hz 40cm.